Sosialisasi Pasal 11 Undang-Undang No.36 Tahun 2009 Tentang Kesehatan - Dyah Listyorini (ADPERTISI, 2022)
Community service by lecturers as a form of one of the Tri Dharma Higher Education activities that must be carried out in the community. This community service activity is to relieve people affected by Covid-19, especially in the Srondol Wetan Village, Semarang, in improving their physical and mental health. During the Covid-19 pandemic, which caused many socio-economic crises in the community, the economy declined and the poverty level of the community increased. Covid-19 is an infectious disease caused by the corona virus, if not handled properly it will cause death. Through community service activities by providing direct health education and providing basic food assistance, it can relieve people affected by Covid-19. By understanding article 11 of Law No. 36 of 2009 concerning health, surely people can realize and improve health for themselves and others, because health is very important for human life.